Departure and conflict management in multi-robot path coordination - Lertkultanon, Puttichai (2020)
This paper addresses the problem of multi-robot path coordination, considering specific features that arise in applications such as automatic aircraft taxiing or driver-less cars coordination. The first feature is departure events: when robots arrive at their destinations (e.g. the runway for takeoff), they can be removed from the coordination diagram. The second feature is the “no-backward-movement” constraint: the robots can only move forward on their assigned paths. These features can interact to give rise to complex conflict situations, which existing planners are unable to solve in practical time. We propose a set of algorithms to efficiently account for these features and validate these algorithms on a realistic model of Charles de Gaulle airport.